Social Networks of Retail Traders: A Case Study of Warung Bugis in Makassar City, Indonesia - Safriadi; Al Isra, Andi Batara (Universitas Andalas, 2025)
This article explores the role of social networks in sustaining traditional retail businesses, with a focus on warung Bugis in Makassar City, Indonesia. The research aims to understand how these networks contribute to the growth and resilience of small enterprises. Through a qualitative approach involving case studies, observations, and interviews, the study examines the factors shaping social and economic interactions among retail traders. Findings reveal that social capital—such as trust, solidarity, and collaboration—is crucial in supporting business resilience. Social networks help traders access resources, share information, and reduce costs while fostering customer loyalty and adapting to modern practices like digital payments and social media marketing. These networks also play a key role in conflict resolution and cooperation among traders, enhancing economic stability. The study highlights the importance of social networks in maintaining competitiveness and offers valuable insights for policymakers to support traditional retail trade in urban areas.